Association of World Bank Policy Lending with Social Development Policies and Institutions - Bogetic, Zeljko (World Bank, Washington, DC, 2017)
Do World Bank policy loans that are focused on social policy reform help improve social policies and institutions in borrower countries? To help answer this question, this paper provides new empirical evidence of the association between World Bank policy lending and measures of the quality of borrower countries' social policies and institutions that such lending supports. Results from estimating a two-stage least squares model indicate that the World Bank's policy lending has a significantly positive effect on the quality of social policies and institutions. The analysis also finds tentative evidence that loan conditions related to social protection and environmental sustainability are more effective in influencing social policies and institutions than those related to equity of public resource use and health and education. In general, the findings are confirmed when estimating a model with a lagged variable of interest. The results suggest that the right kind of conditionality can help improve social policies, therefore providing an important lever for reaching the twin goals of ending extreme poverty and stimulating shared prosperity.